Recognizing women’s hidden role in climate action: Lessons from Eastern Indonesia - Sulastri Sardjo; Elisabeth Yulia Nugraha; Jop Koopman (SIMULACRA: JURNAL SOSIOLOGI, 2026)
The global energy transition is central to addressing climate change and advancing sustainable development. Achieving a just transition requires attention to social and gender dimensions. Yet, in many rural contexts, women are still positioned as passive recipients rather than active contributors to renewable energy initiatives. This study examines women’s recognition and inclusion in the development of household-scale biogas systems in Manggarai Regency, East Nusa Tenggara, Indonesia. Drawing on feminist political ecology and the energy justice framework, the research explores how gendered divisions of labor, situated knowledge, and local power relations shape women’s participation in renewable energy transitions, particularly in livestock management and household energy practices. Fieldwork in Nenu and Pagal villages used a participatory action research approach, combining in-depth interviews and focus group discussions with women farmers and local stakeholders. Findings show that women’s everyday livestock management—feeding animals, maintaining stalls, and collecting manure—is essential for sustaining household biogas systems. These often-invisible forms of labor position women as key actors in maintaining biodigester feedstock. The study contributes by integrating feminist political ecology and energy justice framework to understand better how gendered labor, knowledge, and power shape participation and recognition in renewable energy initiatives.